Green synthesis of hyaluronan fibers with silver nanoparticles - Abdel-Mohsen, A M; Hrdina, Radim; Burgert, Ladislav; Krylová, Gabriela; Abdel-Rahman, Rasha M; Krejčová, Anna; Steinhart, Miloš; Beneš, Ludvík (Carbohydrate polymers, 2012)
The application of green chemistry in the nano-science and technology is very important in the area of the preparation of various materials. In this work, an eco-friendly chemical method was successfully used for the preparation of hyaluronan fibers containing silver nanoparticles (AgNPs). Thus, hyaluronic acid (HA) was dissolved in an aqueous solution of sodium hydroxide to prepare a transparent solution, which was used for the preparation of fibers by a wet-spinning technique. Consequently, silver nanoparticles inside the fiber were prepared. Different parameters affecting the preparation of final product, such as concentration of silver nitrate, hyaluronan fiber concentration, time and temperature of the reaction, pH of the reaction mixture, were studied. AgNPs were confirmed by transmission electron microscopy (TEM), X-ray diffraction (XRD), two-dimensional X-ray scattering (2D SWAXS), UV/Vis spectroscopy, inductively coupled plasma optical emission spectrometry (ICP OES) and scan electron microscopy (SEM). Mechanical properties of prepared fibers were also measured.
Keywords: Green Chemistry Technology; spektrální analýza; Microscopy, Electron, Scanning; X-Ray Diffraction; kyselina hyaluronová; stříbro; Spectrum Analysis; Silver; transmisní elektronová mikroskopie; Hyaluronic Acid; Microscopy, Electron, Transmission; Metal Nanoparticles; kovové nanočástice; difrakce rentgenového záření; technologie zelené chemie; mikroskopie elektronová rastrovací